Assessment of the strength of the trunk and upper limb muscles in stroke subjects with portable dynamometry: a literature review - Júlia Caetano Martins; Luci Fuscaldi Teixeira-Salmela; Larissa Tavares Aguiar; Lucas Araújo Castro e Souza; Eliza Maria Lara; Christina Danielli Coelho de Morais Faria
Introduction Clinical measurements of strength in stroke subjects are usually performed and portable dynamometers are one of the most employed instruments. Objective To verify the standardization procedures of the methods used to assess the strength of the trunk and upper limb muscles with portable dynamometers in stroke subjects, as well as to assess the psychometric properties which were already investigated. Materials and methods An extensive search was performed on the MEDLINE, SciELO, LILACS, and PEDro databases, by combining specific key words, followed by active manual searches by two independent researchers. Results and discussion Fifty-eight studies were included: three related to the trunk and 55 to the upper limb muscles, including handgrip and pinch strength assessments. The most investigated muscular groups were handgrip, elbow flexors/extensors, wrist extensors, and lateral pinch. Nine studies reported adequate reliability levels and the seated position was employed in the majority of the studies which assessed trunk, handgrip, and pinch strength, while the supine position was used for the other muscular groups. The number of trials most used was three, while the reported contractions and rest times were variable. Final considerations Most studies reported the positioning and/or the data collection protocols; however, there was no consensus on the standardization procedures. The only investigated psychometric property was reliability. Few studies evaluated the trunk muscles and other psychometric properties.